2017
DOI: 10.1530/ec-17-0051
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analyses of the steroid metabolome in obese PCOS girls with weight loss

Abstract: ObjectiveThe underlying mechanisms of polycystic ovarian syndrome (PCOS) are not fully understood yet. The aim of the study was to get functional insights into the regulation of steroid hormones in PCOS by steroid metabolomics.DesignThis is a longitudinal study of changes of steroid hormones in 40 obese girls aged 13–16 years (50% with PCOS) participating in a 1-year lifestyle intervention. Girls with and without PCOS were matched to age, BMI and change of weight status.MethodsWe measured progesterone, 17-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Three studies were excluded because of having incomplete outcome data [35], repetitive data [36], and one being a longitudinal design study [37]. The results for risk of bias are shown in Table 2 in the supplementary file.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were excluded because of having incomplete outcome data [35], repetitive data [36], and one being a longitudinal design study [37]. The results for risk of bias are shown in Table 2 in the supplementary file.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to 17OHP, 21DF may be better for diagnosing adults with non-classic CAH due to 21OHD (24, 25). Whether 21DF is better than 17OHP to differentiate other disorders with elevated 17OHP, such as PCOS needs to be evaluated (26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, LC–MS/MS-based longitudinal measurements of androgens were reported in 40 obese girls with adolescent PCOS (33). Interestingly, that study reported elevated A4 and testosterone levels, but normal DHEAS compared to BMI-matched controls.…”
Section: Discussionmentioning
confidence: 99%